Bt toxin in the soybean looper: susceptibility, fitness & selection - Silva, Nilson Rodrigues da (2015)
The soybean looper, Chrysodeixis includens, and the cotton bollworm, Heliothis virescens, (Lepidoptera: Noctuidae), cause significant losses in soybean and cotton in Brazil and are targeted by transgenic Bacillus thuringiensis (Bt) cultivars producing Cry1A and Cry2A toxins. In this study, three experiments were conducted to determine: i) the susceptibility of Brazilian populations of C. includens to Cry1Ac and Cry2Aa as well as the toxicity of these toxins to H. virescens, ii) the lethality and fitness effects on C. includens caused by Bt soybean or cotton producing one or the two toxins, and iii) the response to selection for Cry1Ac resistance to assess the risk of evolution of resistance and cross-resistance to Cry toxins in C. includens. Cotton and soybean cultivars used included two non-Bt isolines, two single-gene Bt cultivars (Cry1Ac cotton and soybean), and two pyramided Bt cottons: (Cry1Ac + Cry2Ab2 and Cry1Ac + Cry1Fa). Diet-surface bioassays showed that susceptibility of C. includens to Cry1Ac and Cry2Aa was variable among the populations tested. LC50 values ranged from 16 to 241 ng/cm2 for Cry1Ac and from 3 to 24 ng/cm2 for Cry2Aa, respectively. Leaf-tissue bioassays with Cry1Ac soybean and pyramided Bt cotton caused 100% mortality of C. includens larvae after two days of exposure. Cry1Ac cotton caused low mortality but negatively affected life-history traits and strongly reduced the net reproductive rate (R0) as well as the intrinsic rate of increase (rm) compared with controls. Selection for Cry1Ac resistance in C. includens using continuous exposure to Cry1Ac cotton during larval development or purified Cry1Ac protein for seven days resulted in 31- and 126- fold resistance with realized heritability of 0.78 and 0.41, respectively, after 12 generations of selection. Importantly, this level of resistance in the Cry1Ac-selected populations was insufficient to allow for survival of larvae in foliage of the Bt soybean producing Cry1Ac. Additionally, soybean loopers of the two laboratory-selected populations showed resistance to Cry1Ab too, but not the Cry2Aa or Cry1Fa in relation to the control, non-selected susceptible population. Taken together, the results of this investigation show that there is natural variation in susceptibility to Cry1Ac and Cry2Aa in the C. includens populations, but the single-toxin Bt soybean and the two- toxin Bt cottons efficiently killed their larvae, indicating that cultivars of these Bt crops should be effective for managing populations of this pest species in field settings. In addition, this study shows that C. includens have potential to evolve relevant resistance levels to Cry1Ac, yet the increase of about 130 fold in the resistance does not allow for survival of neonate soybean loopers in the Bt Cry1Ac soybean. Furthermore, selection for resistance to Cry1Ac did not lead to cross-resistance to Cry2A and Cry1F, suggesting that these two Bt toxins are compatible for resistance management of C. includens.